Data science in the evaluation of the impact of public policies: A literature review - Rosales Reyes, Ganimedes T. (2022)
Ensuring that public policies deliver results that improve people's quality of life has always been a central concern of public decision-makers, especially with budgetary restrictions such as the ones most countries are going through or will go through in the post-pandemic context. On the other hand, data science, artificial intelligence, open data, and, generally, technologies driven by large amounts of data are gaining ground in public management. This article aims to determine the current state of research on the interaction between these two disciplines, studying the application of data science to the impact assessment of public policies and identifying research gaps. A systematic literature review revealed that the proposed object of study has not been at the center of academic research. What has been investigated is the complete cycle of policy development or public management in general. The study also verified that the interaction between public affairs and data science is still an emerging field, and, in the opinion of many academics, what is lacking is research with a holistic vision that sees beyond the eminently technical.